Bahasa Inggris - Nur Huda; Eli Rohaeti; Jaslin Ikhsan (Postgraduate, University of Mataram, 2023)
This study's main objective is to explore chemistry students' attitudes towards the learning policies implemented during the Covid-19 Pandemic. Method: This study used a quantitative approach with a cross-sectional survey method. Respondents were 201 students majoring in chemistry at a university in Surabaya, Indonesia. The data collection instrument was a questionnaire developed during the research and validated through a confirmatory factor analysis (CFA) test. Data analysis used is descriptive statistics and two-way ANOVA test to interpret differences in student perspectives based on two characteristics. Findings: 18 of the 21 questionnaire items fall into the valid and reliable category with a loading factor value greater than 0.50. From the two characteristics of the respondents who were analyzed through the two-way ANOVA test, there were significant differences in student perspectives on the implementation of learning based on learning intensity with significance levels of 0.031. Overall, 52% of students choose blended learning, 46% face-to-face, and 2% online learning. Implications for Research and Practice: Currently, blended learning is still relevant for chemistry students in Indonesia. With notes, face-to-face learning is carried out more than virtual (online) learning, and practical learning in the laboratory is carried out face-to-face in full.